Automation Control Theory Perspectives in Intelligent Systems Proceedings of the 5th Computer Science On-line Conference 2016 (CSOC2016), Vol 3 - Silhavy, Radek; Senkerik, Roman; Oplatkova, Zuzana Kominkova; Silhavy, Petr; Prokopova, Zdenka (Advances in Intelligent Systems and Computing, 2016)
The volume Automation Control Theory Perspectives in Intelligent Systems presents new approaches and methods to real-world problems, and in particular, exploratory research that describes novel approaches in the field of cybernetics and automation control theory. Particular emphasis is laid on modern trends in intelligent information technology, system monitoring and proactive management of complex objects The 5th Computer Science On-line Conference (CSOC2016) is intended to provide an international forum for discussions on the latest high-quality research results in all areas related to Computer Science. The addressed topics are the theoretical aspects and applications of Computer Science, Artificial Intelligences, Cybernetics, Automation Control Theory and Software Engineering.